Changes of human immunodeficiency virus (HIV) burden globally and in China over three decades: a secondary analysis of global HIV statistics. Issue 22 (20th November 2022) - Lu, Yanqiu; Tang, Shengquan; Qin, Yuanyuan; Harypursat, Vijay; Wu, Hao; Chen, Yaokai
Abstract: Background: A more comprehensive understanding of the trends of incidence, prevalence, and mortality in human immunodeficiency virus (HIV), and their complex interrelationships, may provide important evidence for decision-making related to HIV prevention and control. The variances in these indices between different population groups, genders, and ages are critical to decipher evolving patterns of the HIV epidemic in specific populations. Methods: A secondary analysis of relevant data was conducted using data extracted from the Global Burden of Disease study of 2019. HIV/acquired immune deficiency syndrome (AIDS) incidence, prevalence, AIDS-related mortality, and mortality-to-prevalence ratio (MPR) for annual percentage change, average annual percentage change (AAPC), and corresponding 95% confidence intervals (CIs) were calculated using joinpoint regression statistical analysis. Results: The AAPC of HIV/AIDS incidence, prevalence, AIDS-related mortality rate, and MPR were –1.4 (95% CI: –1.6, –1.2), 4.1 (95% CI: 4.0, 4.3), 2.0 (95% CI: 1.7, 2.3), and –2.1 (95% CI: –2.3, –1.8) between 1990 and 2019 globally, and were 3.5 (95% CI: 2.2, 4.8), 6.9 (95% CI: 6.8, 7.0), 8.1 (95% CI: 7.1, 9.1), and 1.2 (95% CI: 0.1, 2.3) in China during the same period. In terms of differences in the preceding indicators by gender, we observed a similar pattern of trends for male and female genders both globally and in China during the entire study period. Each specific age group exhibits a distinct pattern in terms of incidence, prevalence, mortality rate, and MPR both globally and in China. Conclusions: Prevalence and mortality rates of HIV/AIDS have increased between 1990 and 2019 globally and in China. While the incidence rate and MPR have declined globally over the past three decades, these two indicators are observed to present an increasing trend in China. There is a high HIV burden among young and middle-aged adults globally; however, the elderly have a high HIV burden in China. HIV screening at older age should be scaled up, and patients with advanced HIV disease should be provided early with additional care and health resources.